(untitled) (Indian Journal of Animal Production and Management, 2024)
The present investigation was conducted in the Banni area of Kachchh during 2008 to 2012, which is a vast grazing land spread on the 3847 sq km area. The main source of livelihood in the region is rearing of livestock, handicraft and contract based animal grazing system. While the education level of Maldharis is 26.50% and lower than national average, their use of ITK in restraining of animals and conservation of natural resources is unique. Various restraining tools used by them are Dan and Nunjan, Vano / Bagari, Pavro, Kutopado, Ango Mochi and Bundho. They also use “kudo” in goat and “Dan” to restrain the movement of camel for grazing and “Bagari” to protect the camel from suckling by the calf. The use of psychological tools like voice produced by different size of bells (mutter or matri) and keeping all the animals in the herd intact during grazing either during day or night hours without any human assistance is the best example of management of animals on the scientific principles. Similarly, harvesting and conservation of rain water in the “Khuriya” is also a unique example of conservation of natural resources. They allow their buffaloes in the dry pond which prevent heat stress and also protection from mosquitoes. They use Khurjadi for transportation of small ruminants, “Dambh” for identification of animals and for housing the calves under the tree shade by making the enclosure called as “Vado.” These techniques are based on scientific principles and have very good impact on animal management.